Development of the device for assisting standing movement from floor - Jun NANGO; Yoshikazu SATO; Shinpei MIURA (Nihon Kikai Gakkai ronbunshu, 2016)
The action of standing up is a starting point when we move to the next actions, and that is performed frequently in daily life. This action induces the pain in joints as people age. Supporting to the action of standing up is important to prevent the nursing care level from advancing. In this research, we develop the mechanism for assisting standing movement from the low position that can set on the floor in the japanese-style room. Double pantagraph jacks are used to expand the operating range of seat plate. We design linkage to follow two postures of legs. Namely, these are starting posture, and ending posture of the standing up motion. Generally, it is difficult to raise the heavy body with the jack in the lowest position because the motion transmissibility can't be gained sufficiently. The mechanism to drive the seat plate is installed under the armrest in order to make the start position of standing lower enough. The length of the link composing the jack is determined to get the height of the seat plate enough to assist the ending posture of the standing up motion. The position where the two links are connected to make them intersecting is indicated as an internally dividing point. This intersecting position of links is determined to make the seat plate follow the attitude of human leg. There are five choices of length of link, and there are four choices of the intersecting position of links, so it is possible to make twenty combinations. From twenty combinations, the best combination is determined by the method of considering the space occupied by the mechanism and the output height and the attitude of the seat plate. The gas spring is used as the power source, the specification of the power source is gained by the static analysis. The experimental device is manufactured using the parameter determined from twenty combinations. It is verified that the seat plate of the experimental device follow the two posture. We evaluate this device's supporting performance by the floor reaction force and the electromyogram of the leg. From the result of measurement of the floor reaction force, the reduction of the physical load is verified. From the result of surface myogenic potential, the muscle activities of the anterior tibial muscle and the gastrocnemius muscle are reduced by using the assist device. On the other hand, the muscle activities of the rectus femoris muscle and the semitendinous aren't reduced very much. It is seemed that the power unit is needed to improve to support in the lower position sufficiently. Points to be noted so as to design the driving source using linear springs are shown.